PUDARNYA KONSEP DIRI: Jeritan Psikologis Siswa Anak TKI SMPN 04 Bandar Batang - Maskhur; Moh. Slamet Untung; Maemonah (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2012)
The object of this study is the students of SMPN 4 Batang Bandar Central Java. It focused on their psycological side relating to their self-concepts. It is a qualitative-phenomenological reasearch. To collect data, it use self-report, rating scale, observation the studentsí behavior, in-depth interviews and caregiver. Based on the data and analysis, it can be concluded that their self-concepts have changed from positive to negative (faded) through successive stages, whether the stages were experienced by them in a whole or in a part. Therefore, the strategy to recover them is needed.